Rekonstruksi Identitas Nasional Dalam Menciptakan Kohesi Sosial di Afrika Selatan Pada Piala Dunia 2010 - Tama, Ricky Yoga; Kumala Dewi, Putu Ratih; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
Identity crisis is the main source in most of social conflicts in south Africa. Forms of social conflicts like race conflicts and xenophobias become barriers for social cohesion building process in South Africa. As an effort to build social cohesion, South Africa Government use national identity to boost its social cohesion. World Cup 2010 becomes platform for the government to utilize national identity as tool to boost the reconciliation process in South Africa soicety.Indicators that forms the social cohesion can be seen through three atributes that build social cohesion, those are inclusive identity, trust, and cooperate for common goods. Through this research, author will discuss about how the South Africa Government utilize national identity to build social cohesion during World Cup 2010 event. Therefore, author will use the concept of social cohesion and national identity theory to describe the government method to utilize national identity to build social cohesion.